Reverse Solvatochromism of Imine Dyes Comprised of 5-Nitrofuran-2-Yl or 5-Nitrothiophen-2-Yl as Electron Acceptor and Phenolate as Electron Donor - Caroli-Rezende, M (Wiley-VCH Verlag, 2018)
Eight compounds with phenols as electron-donating groups and 5-nitrothiophen-2-yl or 5-nitrofuran-2-yl acceptor moieties in their molecular structures were synthesized. The crystalline structures of six compounds were obtained. Their corresponding phenolate dyes were studied in 29 solvents and the data showed that in all cases a reverse solvatochromism occurred. The results are explained in terms of the ability of the medium to stabilize the electronic ground and excited states of the probes to different extents. The frontier molecular orbitals were analyzed for the protonated and deprotonated forms of the compounds. The calculated geometries are in agreement with the X-ray structures determined for the compounds and it was verified that after their deprotonation an increase in the electron delocalization occurs. Radial distribution functions were calculated for the dyes in water and n-hexane to analyze different solvation patterns resulting from the interaction of the solvents with the dyes. Data obtained by using the Catalán multiparameter equation revealed that the medium acidity is responsible for hypsochromic shifts, whereas the solvent basicity, polarizability, and dipolarity contributed to bathochromic shifts of the solvatochromic band of these dyes. Two model “hybrid cyanine” dyes were used in the design of simple experiments to demonstrate that the solvatochromic behavior of these dyes in solution can be tuned with careful consideration of the properties of the medium. © 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim